2017
DOI: 10.1007/s11244-017-0819-8
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic Degradation of Perfluorooctanoic Acid (PFOA) From Wastewaters by TiO2, In2O3 and Ga2O3 Catalysts

Abstract: 14The aim of the work was to prepare nanosized In2O3 and Ga2O3 photocatalysts for degradation of 15Perfluorooctanoic acid (PFOA) in water. Their commercial references along with TiO2 were used as 16 a comparison basis. The characterization of the materials proved that successful preparation of cubic 17In2O3 and monoclinic ß-Ga2O3 were achieved via solvothermal and hydrothermal methods, 18 respectively. The effect of different parameters such as catalyst dosage, UV light source and 19 utilization of inorganic o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…TiO 2 -based photocatalysts Notably, TiO 2 -based photocatalysts are the most commonly studied photocatalytic materials for the destruction of PFOA. Many kinds of bulk TiO 2 , including commercial Degussa P25, 55,59 Degussa Evonik P25, 29,60,61 Aeroxide P25, 62 (Riedel-de Haen, Seelze, Germany, 10.3 m 2 g −1 ), 33 TiO 2 (RdH), 41 and TiO 2 (solgel), 41,63 have been extensively examined with the irradiation of UV light. However, bulk TiO 2 performs a low photocatalytic activity and is not applicable in practice.…”
Section: Tailoring Of Photocatalysts For Degradation Of Perfluorocarbmentioning
confidence: 99%
See 2 more Smart Citations
“…TiO 2 -based photocatalysts Notably, TiO 2 -based photocatalysts are the most commonly studied photocatalytic materials for the destruction of PFOA. Many kinds of bulk TiO 2 , including commercial Degussa P25, 55,59 Degussa Evonik P25, 29,60,61 Aeroxide P25, 62 (Riedel-de Haen, Seelze, Germany, 10.3 m 2 g −1 ), 33 TiO 2 (RdH), 41 and TiO 2 (solgel), 41,63 have been extensively examined with the irradiation of UV light. However, bulk TiO 2 performs a low photocatalytic activity and is not applicable in practice.…”
Section: Tailoring Of Photocatalysts For Degradation Of Perfluorocarbmentioning
confidence: 99%
“…72 Ga 2 O 3 -based photocatalysts Nanostructured Ga 2 O 3 has also received attention, which exhibits wide bandgap semiconductor (bandgap >3.0 eV), interesting photoluminescence, excellent conduction, and tunable optical properties. 73 Diverse nanostructures of Ga 2 O 3 have been synthesized and applied successfully for photodegradation of PFOA, including nanoparticles, 52 monoclinic rod-shaped crystals, 62 needle-like, 74 and sheaf-like nanomaterial. 75 In general, the photogenerated electron of Ga 2 O 3 has much higher reductive capability than that of TiO 2 , the PFOA molecules, which adsorb on Ga 2 O 3 surface, could be more easily attacked by photogenerated electrons than that on TiO 2 , resulting in enhancing photocatalytic activity over Ga 2 O 3 .…”
Section: Doping With the Metal Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among them, α‐Ga 2 O 3 ( a =4.58 Å, b =9.80 Å, c =2.97 Å) and β‐Ga 2 O 3 were investigated as the most common photocatalysts [Figure (b)] and were synthesized using the solvothermal process or hydrothermal method . It has been shown that Ga 2 O 3 exhibits acceptable photocatalytic properties to degrade different pollutants or wastewater under solar‐light irradiation . Park et al.…”
Section: The Preparation and Related Applications Of Lm Catalystsmentioning
confidence: 99%
“…[54] It has been shown that Ga 2 O 3 exhibits acceptable photocatalyt-ic properties to degrade different pollutants or wastewater under solar-light irradiation. [35] Park et al reported novel mesoporousand macroporous Ga 2 O 3 spindles that achieved efficient photocatalytic conversion of CO 2 into CH 4 , [34a] as shown in Figure 6(a). Doping Ga 2 O 3 with different metals,i ncluding Pb, [37] Pd, [38] Ni, [36] Zn, [37] Ag, [39b] Au [ Figure 6(c-e)],h ave also been also investigated to overcome the constraints of photocatalytic activities.…”
Section: Lm Catalysts For the Generation Of Hmentioning
confidence: 99%